Prediction of cardiovascular events in patients with chronic myeloid leukaemia using baseline risk factors and coronary artery calcium scoring. Issue 10 (18th October 2021) - Baggio, Diva; Tan, Sean; Porch, Kylie; Shortt, Jake; Ko, Brian
Abstract: A standardised method for cardiovascular risk stratification in chronic myeloid leukaemia patients treated with tyrosine kinase inhibitors is lacking. We report an algorithm for risk stratification applicable to all patients commencing tyrosine kinase inhibitor therapy based on age, prior cardiovascular disease and Framingham Risk Score, incorporating coronary artery calcium scoring in patients at intermediate Framingham Risk Score risk. Of 88 patients retrospectively studied, major adverse cardiovascular event rates in our study‐defined low‐, intermediate‐ and high‐risk categories were 0%, 10% and 19% respectively. Of nine patients down‐classified from intermediate to low risk on the basis of coronary artery calcium scoring, none went on to experience a major adverse cardiovascular event.